Radiation therapist health literacy training: Does learning alternate communication methods translate into improved confidence in patient interactions?. Issue 3 (August 2020) - Kelly, T.; Arnold, B.; Surjan, Y.; Rinks, M.; Warren-Forward, H.
Abstract: Introduction: Low health literacy can inhibit patients' understanding of radiation therapy (RT) procedures. An objective of this research was to develop training to educate Australian radiation therapists (RTTs) about tools that support low health literacy patients, namely plain language and the Teach Back method (TBM). Perceptions, clinical use of these tools and confidence levels (pre and post training) in occupational scenarios were evaluated. Methods: RTTs attended two workshops one week apart. Three anonymous surveys (before the first workshop, immediately after the second and three months post workshops) were completed. Quantitative analysis included weighted sum averages of confidence levels and chi-square analysis. Results: At baseline, 56% of participants had heard of 'health literacy', 93% 'plain language', while 26% knew about TBM. Confidence levels increased after the workshops, with improvement of confidence demonstrating significance ( p < 0.05 ) in 3/7 scenarios. The use of 'plain language' assessed on the third survey during every interaction was higher than that anticipated by participants on the second survey (46% vs 39%), while the TBM was utilised less (0% vs 23%). Conclusion: Radiation therapists' confidence and use of alternative tools to improve patient understanding improved after attending training. Implications for practice: Ongoing encouragement using alternate communication methods are recommended to assist with strengthening patient outcomes.